Human Papillomavirus Vaccination in Saudi Arabia: A Narrative Review of Current Evidence - Abdulrahman M. M. Alqahtani; Mohammed S. S. Alshahrani; Ebtesam Almajed; Rawan A. Bin Salamah; Norah Alqntash; Amina M. Biju; Mohima S. Meem; Fawaz Pullishery (Journal of Pharmacy and Bioallied Sciences)
Human papillomavirus (HPV) represents the most common sexually transmitted infection globally, exerting a substantial impact on sexual and reproductive health, with a high oncogenic potential leading to various malignancies. The prevalence of HPV in Saudi Arabia ranges from 9% to 43%, with types 16, 18, and 45 being the most common high-risk strains. Despite the availability of effective vaccines such as Gardasil 9, Gardasil, and Cervarix, proper awareness and vaccination rates remain low in Saudi Arabia. Only 4% of the population has received the HPV vaccine. The Saudi Ministry of Health has integrated HPV vaccines into the national immunization schedule, offering them free of charge and ensuring their availability for adolescent girls and women. However, challenges persist, including cultural and religious beliefs, inadequate healthcare infrastructure, and insufficient public awareness. To effectively increase HPV vaccination coverage, it is crucial to implement comprehensive public education campaigns, actively involve healthcare professionals, and address cultural and religious concerns with sensitivity and respect. International collaboration, such as initiatives by the Gavi alliance and sustained research efforts, is critical to optimizing HPV vaccine efficacy, accessibility, and uptake. Through coordinated efforts, the global burden of HPV-related diseases can be significantly reduced, ultimately leading to improved public health outcomes.